2017
DOI: 10.1080/22423982.2017.1345277
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Community Conversations About Research to End Suicide: learning and behavioural outcomes of a training-of-trainers model to facilitate grassroots community health education to address Indigenous youth suicide prevention

Abstract: Alaska Native (AN) youth suicide remains a substantial and recalcitrant health disparity, especially in rural/remote communities. Promoting Community Conversations About Research to End Suicide (PC CARES) is a community health intervention that responds to the need for culturally responsive and evidence-supported prevention practice, using a grassroots approach to spark multilevel and community-based efforts for suicide prevention. This paper describes theoretical and practical considerations of the approach, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…These principles are in direct conflict with the Indigenous perspective of wholistic healing. The Western method of focusing on the individual, and the risk factors associated with that person, leave aside what is known about the sociocultural, economic and historical experiences Indigenous communities may have endured as a whole and the effects these may have had on individual youth (Barker et al, 2017;Wexler et al, 2017).…”
Section: Differences Between Western and Indigenous Perspectives On Cmentioning
confidence: 99%
See 4 more Smart Citations
“…These principles are in direct conflict with the Indigenous perspective of wholistic healing. The Western method of focusing on the individual, and the risk factors associated with that person, leave aside what is known about the sociocultural, economic and historical experiences Indigenous communities may have endured as a whole and the effects these may have had on individual youth (Barker et al, 2017;Wexler et al, 2017).…”
Section: Differences Between Western and Indigenous Perspectives On Cmentioning
confidence: 99%
“…Of the contributing factors to Indigenous youth suicide identified in this literature review, colonization was among the most detrimental and the most commonly identified by scholars who considered Indigenous perspectives in their work. Indigenous scholars recognize historical and intergenerational impacts of colonization which are widely understood within Indigenous perspectives as a key contributing factor to suicide among Indigenous youth (Duran, 2019;Wexler et al, 2017). This was in contrast to dominant Western perspectives in the literature which tended to focus on psychological factors to explain and respond to Indigenous youth suicide (Burrage et al, 2016).…”
Section: Causes Of Indigenous Youth Suicidementioning
confidence: 99%
See 3 more Smart Citations